Ultra-Wideband Geo-Regioning: A Novel Clustering and Localization Technique. (13th December 2007) - Steiner Steiner, Christoph Christoph; Althaus Althaus, Frank Frank; Troesch Troesch, Florian Florian; Wittneben Wittneben, Armin Armin
Abstract : Ultra-wideband (UWB) technology enables a high temporal resolution of the propagation channel. Consequently, a channel impulse response between transmitter and receiver can be interpreted as signature for their relative positions. If the position of the receiver is known, the channel impulse response indicates the position of the transmitter and vice versa. This work introduces UWB geo-regioning as a clustering and localization method based on channel impulse response fingerprinting, develops a theoretical framework for performance analysis, and evaluates this approach by means of performance results based on measured channel impulse responses. Complexity issues are discussed and performance dependencies on signal-to-noise ratio, a priori knowledge, observation window, and system bandwidth are investigated.